Pengaruh Indikator Moneter dan Harga Minyak Dunia Terhadap Indeks Harga Saham Gabungan - Reggi Zaki Mubarok; Rifki Khoirudin (EKONOMI & SOSIAL, 2023)
Developments in a country's economic conditions affect the flow of capital, economic growth and state tax revenues. When investment is high, capital flows also increase so that the economy is moved and affects economic growth and state revenues increase due to taxes paid by companies. The Covid 19 outbreak which affected the movement of the JCI greatly impacted the economy and a drop in the JCI could become a problem in Indonesia. The purpose of this study was to determine the effect of inflation, The Fed Interest Rate, BI Interest Rate, JUB (M1) and World Oil Prices on the Composite Stock Price Index in Indonesia. In this study, data were taken from secondary data by collecting data taken from the official website. The type of data used in quantitative data is data related to a number or nominal, which is obtained from a systematic calculation. The time series horizon for the period 2017-2021 (monthly data) comes from the Central Statistics Agency (BPS), Ministry of Finance, Bank Indonesia (BI), Organization of the Petroleum Exporting Countries (OPEC). This study uses a data analysis method, namely the Multiple Regression Analysis Model. Based on the results of the analysis, the results of this study prove that the Fed Interest Rate has a positive and significant effect and the BI Interest Rate has a negative and significant effect on the JCI while Inflation, JUB (M1) and World oil prices have no effect on the JCI.